Minerals identification and characterization using a new 3D printed composite- structured split ring resonator microwave sensor - Madan Kumar Sharma; Nadir Kamal Salih Idries; Abdullah Said Alkalbani; Degala Satyanarayana; Gopal Rathinam; Ankit Sharma (Discover Applied Sciences)
Abstract The identification of minerals is crucial for optimizing economic and environmental strategies worldwide. This study presents a novel approach to mineral identification and characterization using microwave sensing technology. The method is specifically designed to identify and characterize copper, chromite, and limestone within Oman’s geological landscape. A 3D-printed, composite-structured Split-Ring Resonator (SRR) Microwave Sensor (MW-sensor) is developed and validated. The sensor, constructed on a 40 mm × 100 mm Roger5880 substrate, incorporates a square-shaped SRR structure positioned between two hexagonal-shaped SRR structures. The sensor is offered multi-resonating points at the frequency (2 GHz, 4.5 GHz and 5.2 GHz) over a wide frequency range 2–10 GHz. The fabricated prototype demonstrated strong alignment with simulation studies. Experiments were conducted on both ideal and mining samples, revealing high sensitivity for copper (75.9%), chromite (75%), and limestone (77.44%). The SRR structures of the sensor exhibit a strong electric-field distribution, which is significantly influenced by the sample being tested. Correlation analysis of reflection results indicated a close match between ideal and mining samples, with maximum correlation coefficients of 0.857 for copper and 0.695 for chromite at 20% Wt./Vol., and 0.792 for limestone at 10% Wt./Vol. These results underscore the potential of the proposed MW-sensor as a cost-effective alternative to existing mineral detection technologies.